Mixed Epithelial and Stromal Tumor of the Kidney in a Patient With Mental Retardation: A Case Report - Kazuki Sato; Kotaro Hirai; Yumiko Yokomizo; Azumi Fujioka; Yuki Ito; Sawako Chiba; Junichi Murayama (IJU Case Reports)
ABSTRACT Introduction Mixed epithelial and stromal tumors are rare renal neoplasms. Case Presentation A 55‐year‐old woman with mental retardation presented with a giant renal tumor with abdominal pain. After a renal biopsy with a definitive diagnosis, an open total nephrectomy was performed. There was no recurrence for the following year. Clinical Discussion Since a definitive diagnosis of MEST cannot be made through imaging alone, surgery is the preferred diagnostic treatment. To our knowledge, renal biopsy has only been reported in three cases. There are only two reports of nonsurgical treatment of benign MEST and no reports of malignant transformation or exacerbation. Conclusion If the biopsy findings are suggestive of a benign tumor, follow‐up is an option. We look forward to reporting the long‐term outcomes of the conservative management of MEST.